Similar appearance, different mechanisms: xerosis in HIV, atopic dermatitis and ageing. Issue 6 (June 2014) - Mischo, Meike; von Kobyletzki, Laura B.; Bründermann, Erik; Schmidt, Diedrich A.; Potthoff, Anja; Brockmeyer, Norbert H.; Havenith, Martina
Abstract Xerosis is one of the most common dermatologic disorders occurring in the elderly and in patients with atopic dermatitis (AD) and human immunodeficiency virus (HIV) infection. Xerosis has been linked to an impaired skin barrier function of the stratum corneum. Using Raman microspectroscopy, we concentrated on deeper skin layers, viable epidermis and dermis of 47 volunteers and associated molecular alterations to the evolution of xerosis and the skin barrier, for example, lipid, water and antioxidant content. A decrease in lipids within the viable epidermis is found for elderly and HIV‐patients. Lipid and water values of AD patients and their healthy reference group are similar. Decreases in lipids and simultaneous increases in water are found in the dermis for HIV and AD patients in comparison to their healthy reference groups. Excessive levels of epidermal carotenoids, mainly lycopene, in HIV‐patients were found potentially leading to adverse effects such as premature skin ageing.